Understanding the Needs of Civil Protection Agencies and Opportunities for Scaling up Disaster Risk Management Investments - World Bank (World Bank, Washington, DC, 2021)
The objective of this report is to summarize insights and provide recommendations related to the challenges and opportunities for civil protection (CP) agencies to leverage investments for disaster prevention and preparedness. This report draws on the findings of stakeholder consultations and desk review. The consultation process, by design, aimed at collecting a wide range of views from a mix of selected countries. The results provide a synthetic view of key challenges and opportunities from the perspective of fourteen countries with diverse disaster risk management (DRM) systems, financial mechanisms, institutional capacity, and exposure to disasters. The consultation process was complemented by desk research of relevant national strategic DRM documents, results of previous similar surveys, information on the use of European Union (EU) funds for DRM, and relevant literature. The report’s findings can inform DG ECHO’s discussions and decisions related to funding provided to CP agencies. This summary report is accompanied by a technical background report.